Implementação da ferramenta My Abilities First em centros especializados em reabilitação para crianças e adolescentes com deficiência - Alencar, Roselene Ferreira de (2024)
Introduction: The My Abilities First (MAF) tool is an educational approach that employs inclusive technology focused on the abilities of individuals with disabilities. The successful implementation of MAF depends, among other factors, on the training of professionals, caregivers, and the individuals with disabilities themselves to ensure effective use with a positive impact. Objective: To structure a model for implementing the MAF tool and analyze the barriers and facilitators from the perspectives of professionals, children with disabilities, and their caregivers. Method: This thesis encompasses qualitative, reflective, and interpretative research based on Participatory Action Research (PAR) and Patient and Public Involvement (PPI). Data analysis was performed using Reflexive Thematic Analysis (RTA). A total of 28 participants, including 12 physical therapists, 4 occupational therapists, 10 children, and 2 adolescents accompanied by their caregivers, responded to a sociodemographic questionnaire, semi-structured interviews, and participated in workshops and focus groups on two themes: Positive Approaches in Health and the MAF Tool. The study was approved by a local ethics committee, opinion number 4.779.175. This doctoral thesis comprised a study titled "Implementation of the My Abilities First Tool in Specialized Rehabilitation Centers for Children and Adolescents with Disabilities," which resulted in 3 articles. Results and conclusions: Article I, "Implementation of the My Abilities First Tool for Empowerment of Children and Adolescents with Disabilities: A Study Protocol," presented literary, ethical, and methodological aspects that guided the subsequent articles; Article II, "Implementation of the My Abilities First Tool: a qualitative study on the perceptions of professionals, caregivers, children, and adolescents with disabilities," identified 2 themes: (1) Perceptions of the MAF tool as an educational process contributing to enhance the inclusion and participation of children and adolescents with disabilities, and (2) Barriers and facilitators for the implementation process of the MAF tool. The implementation of the MAF tool was mentioned as a driver in promoting equity and increasing the participation of children and adolescents with disabilities in various contexts, including health, education, and leisure; Article III, "Implementation of the My Abilities First Tool: a qualitative study on the experiences of professionals, children/adolescents with disabilities, and caregivers," identified 3 themes: (1) Perceptions of physical therapists, occupational therapists, children and adolescents with disabilities, and their caregivers regarding positive health attitudes and the appreciation of abilities, (2) Attitude change towards the abilities of children and adolescents with disabilities, and (3) Facilitators and barriers in the implementation of the MAF tool. These 3 themes reflect the participants' understanding and experiences with MAF in the routine of children and adolescents with disabilities and the process to implement it. The implementation of the MAF tool was recognized as an innovation due to its ability-centered approach. The need to address social, attitudinal, communication, and information barriers to adapt and apply the tool more effectively in health, school, and leisure settings was noted. The appreciation of the abilities of children and adolescents was recognized to better promote inclusion and participation.